2017
DOI: 10.1371/journal.pcbi.1005384
|View full text |Cite
|
Sign up to set email alerts
|

Co-emergence of multi-scale cortical activities of irregular firing, oscillations and avalanches achieves cost-efficient information capacity

Abstract: The brain is highly energy consuming, therefore is under strong selective pressure to achieve cost-efficiency in both cortical connectivities and activities. However, cost-efficiency as a design principle for cortical activities has been rarely studied. Especially it is not clear how cost-efficiency is related to ubiquitously observed multi-scale properties: irregular firing, oscillations and neuronal avalanches. Here we demonstrate that these prominent properties can be simultaneously observed in a generic, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 84 publications
(128 reference statements)
5
50
0
Order By: Relevance
“…Consistent with experimental observations, recent investigations have shown that avalanches of neuronal activity preferentially emerge at a moderately synchronized state of collective firing activity and might coexist with both irregular firing and stochastic oscillations (Gireesh & Plenz, 2008;Lubenov & Siapas, 2008;Yang, et al, 2017). Notably, this finding is of particular interest because the co-emergence of these multi-scale cortical activities has been believed to ensure the cost-efficient information capacity of the brain, further emphasizing the functional significance of avalanche dynamics in neuronal information processing (Yang, et al, 2017).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with experimental observations, recent investigations have shown that avalanches of neuronal activity preferentially emerge at a moderately synchronized state of collective firing activity and might coexist with both irregular firing and stochastic oscillations (Gireesh & Plenz, 2008;Lubenov & Siapas, 2008;Yang, et al, 2017). Notably, this finding is of particular interest because the co-emergence of these multi-scale cortical activities has been believed to ensure the cost-efficient information capacity of the brain, further emphasizing the functional significance of avalanche dynamics in neuronal information processing (Yang, et al, 2017).…”
Section: Introductionsupporting
confidence: 62%
“…Recent experimental and computational studies have emphasized that avalanches of neuronal activity may emerge when there is moderately synchronous firing of neurons (Gireesh & Plenz, 2008;Lubenov & Siapas, 2008;Yang, et al, 2017). To examine whether the critical neuronal avalanches can also be triggered by the structural heterogeneity in synaptic connectivity, we for networks with input heterogeneity.…”
Section: Heterogeneous Input Connectivity Evokes and Regulates Neuronmentioning
confidence: 99%
“…Research in this field has also suggested that information storage and capacitythe ability of a system to encode a broad repertoire of complex states from which information can be decoded (Gatlin, 1972)-may be optimized at criticality. Again, this notion has been captured in simple neural models (Bertschinger and Natschläger, 2004;Haldeman and Beggs, 2005;Yang et al, 2017) and also demonstrated in empirical recordings, including those arising in unperturbed (resting state) recordings (Breakspear, 2001;Deco and Jirsa, 2012) as well as through careful pharmacological manipulations of in vivo neurophysiological recordings (Stewart and Plenz, 2006). Selective enhancement of weak (but not strong) stimuli also occurs near a phase transition (Copelli, 2014).…”
Section: Computational Aspects Of Neuronal Criticalitymentioning
confidence: 90%
“…Therefore, most likely the basic principle of a trade-off between physical cost and functional values could be operating to shape the network structure and dynamics across different levels. Our own recent work [ 70 ] showed that the co-organization of salient multi-scale dynamical features as typically observed in electrophysiological experiments, including irregular firing of individual neurons, clustered firing of neuron groups in the form of critical avalanches and the emergence of stochastic oscillations of the population, indeed reflects a cost-efficient neuronal information capacity with economical firing rates. In the future, it will be important to study cost-efficiency trade-offs in an integrated manner in terms of both neuronal connectivity and activity and in specific neuronal information processing tasks across multiple levels of brain organization.…”
Section: Discussionmentioning
confidence: 99%